Zeolite reactions in the Smrekovec volcanics, Northern Slovenia - Kralj, Polona (Geologija, 2001)
Upper Oligocene Smrekovec volcanics are characterised by the occurrence of zeolites, developed under hydrothermal conditions in the vicinity of the main crater and shallow intrusive bodies. Zeolitisation is the most pronounced in coarse-grained volcaniclastic rocks. The most widespread zeolite is laumontite, which occurs as a replacement of the primary constituents, volcanic glass and plagioclases, as interstitial filling and vein mineral. Sometimes, laumontite replaces prehnite, which developed at higher temperatures and became unstable when the chemistry and temperature of hydrothermal fluids changed. Locally, laumontite is replaced by analcime, mordenite, clinoptilolite and heulandite. The zeolite reactions are related primarily to the changes in chemical composition of reacting fluids, particularly to increased activities of SiO2, and the H+ and Na+ ions.